B Cell Lymphoma, Unclassifiable, Transformed from Follicular Lymphoma: A Rare Presentation with Review of the Literature - Anila Kanna; Swati Agrawal; Kumar Jayant; Varun Kumar Pala; Mohammad Altujjar; Tarik Hadid; Muhammad Khurram (Case Reports in Hematology)
B cell lymphoma, unclassifiable, with features of diffuse large B cell lymphoma and classical Hodgkin’s lymphoma (BCLu-DLBCL/CHL) is more commonly known as gray zone lymphoma. These cases more often present with mediastinal disease. In this report, we present a very rare case of BCLu-DLBCL/CHL without mediastinal involvement, transformed from follicular lymphoma (FL) to BCLu-DLBCL/CHL. This patient initially presented with a mass in the right neck; biopsy of the lymph node showed predominantly nodular, follicular pattern. Immunohistochemical (IHC) staining of tumor cells expressed positivity for mature B cell markers CD20, CD19, CD10, CD23, CD45, and CD38 but negative for CD5,11c. Hence, diagnosed with FL, he was given rituximab, cyclophosphamide, vincristine, and prednisone (RCVP) regimen, followed by maintenance rituximab. He showed good response. After 2 years, he presented again with a mass in the right side of the neck. Although the needle core biopsy of this mass was suggestive of B cell lymphoma, excisional biopsy showed morphological features of DLBCL as well as foci of histological pattern of CHL. IHC staining expressed positivity for CD20, CD79a, PAX5, and CD15 and CD30 consistent with DLBCL and CHL. He was diagnosed with BCLu-DLBCL/CHL. The patient received “ACVBP” (doxorubicin, cyclophosphamide, vindesine, bleomycin, and prednisone) followed by radiation. BCLu-DLBCL/CHL is clinically an aggressive tumor with poorer outcomes, but our case showed complete response to ACVBP regimen with tumor regression.